2020
DOI: 10.7181/acfs.2020.00192
|View full text |Cite
|
Sign up to set email alerts
|

Bone remodeling after conservative treatment of nasal bone fracture in pediatric patients

Abstract: Background: The standard treatment of nasal bone fractures in pediatric patients is closed reduction. Conservative treatment is sometimes performed, but poses a risk of nasal deformity. The aim of this study was to evaluate the outcomes of bone remodeling in pediatric nasal fractures. Methods: Information was extracted from the medical records of patients under 12 years of age who received conservative treatment for a nasal bone fracture and underwent follow-up computed tomography (CT) examinations. The initia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 10 publications
1
8
0
Order By: Relevance
“…X-ray imaging may not provide an exact examination of pediatric nasal bone fractures during the recovery period because nasal fractures that have not completely ossified may be inadequately determined. 16 Overall, the results of our study indicated that the number of nasal fracture cases decreased during the pandemic period compared to the 1-year period before the pandemic. We observed the most common fracture type to be the IIA nasal fracture.…”
Section: Discussionsupporting
confidence: 48%
“…X-ray imaging may not provide an exact examination of pediatric nasal bone fractures during the recovery period because nasal fractures that have not completely ossified may be inadequately determined. 16 Overall, the results of our study indicated that the number of nasal fracture cases decreased during the pandemic period compared to the 1-year period before the pandemic. We observed the most common fracture type to be the IIA nasal fracture.…”
Section: Discussionsupporting
confidence: 48%
“…The follow-up results were favorable, without nasal skeletal asymmetry or irregularity. The other patients who received conservative treatment did not undergo follow-up CT examinations, and did not show any nasal deformity or discomfort at 1 month after the initial injury, and based on these results, favorable bone remodeling could be expected after long-term follow-up in minor adolescent nasal fractures, as in the pediatric nasal bone fracture [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…The outcome was considered excellent if there was no malalignment of the fracture segment, bony irregularity, or displacement, and good if there was mild malalignment of the fracture segment with one segment of bony irregularity or displacement. A fair outcome was defined as an irregular nasal pyramid with malalignment, bony irregularity, and displacement ( Table 1 ) [ 10 ].…”
Section: Methodsmentioning
confidence: 99%